Reconstruction of Court Decisions in the Implementation of a Fair Restorative Justice Mechanism for Defendants Under the National Criminal Procedure Code - Ryzza Dharma; Zudan Arief Fakrulloh (Journal Customary Law, 2026)
The enactment of Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code (KUHAP Nasional) marks a paradigmatic shift from retributive justice toward restorative justice within the criminal justice system. However, this transformation reveals a significant normative inconsistency, particularly in the limitation of judicial authority under Article 203, which restricts judges from terminating cases based on restorative outcomes and instead positions such outcomes merely as mitigating factors in sentencing. This study employs a normative juridical method with statutory and conceptual approaches to examine the disparity in the application of restorative justice across the stages of investigation, prosecution, and adjudication. The findings demonstrate that while law enforcement officials at the pre-adjudication stage are authorized to terminate cases without a declaration of guilt, judges remain bound to issue guilty verdicts even when full reconciliation between the offender and victim has been achieved. This disparity results in systemic injustice and produces an “invisible punishment” in the form of criminal records that hinder the offender’s social reintegration. To address this issue, the study proposes a reconstruction of judicial decisions through the introduction of a “Restorative-Based Case Termination Order,” enabling judges to terminate proceedings without imposing criminal labels. This model aims to harmonize the criminal justice system and promote substantive justice by aligning legal outcomes with the core principles of restorative justice.